2005
DOI: 10.1111/j.1365-2036.2005.02404.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of transcatheter arterial embolization for patients with unresectable hepatocellular carcinoma: a nationwide, multicentre study evaluated by cancer stage

Abstract: SUMMARYBackground: Transcatheter arterial embolization is a major palliative treatment for unresectable hepatocellular carcinoma, but the survival benefit of transcatheter arterial embolization is controversial. Aim: To evaluate the role of transcatheter arterial embolization in different stage of unresectable hepatocellular carcinoma and to select patients who can get the best benefit from the treatment. Methods: From 1991 to 1995, 476 patients who had unresectable hepatocellular carcinoma from four medical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 29 publications
1
28
1
Order By: Relevance
“…The HCC nodule(s) was considered unresectable if there were multifocal lesions which made extended resection necessary to eradicate all tumors, or hepatic reserve was insufficient with an indocyanine green 15-min retention rate > 30%. The criteria for patients undergoing TACE were: (1) no main portal vein trunk involvement or extrahepatic metastasis, (2) CTP functional class A or B, (3) normal renal function with a serum creatinine concentration < 1.5 mg/dL, and (4) no gross ascites by ultrasound or CT [24, 25]. Therapeutic information including benefits and risks was provided to individual patient based on shared decision making.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HCC nodule(s) was considered unresectable if there were multifocal lesions which made extended resection necessary to eradicate all tumors, or hepatic reserve was insufficient with an indocyanine green 15-min retention rate > 30%. The criteria for patients undergoing TACE were: (1) no main portal vein trunk involvement or extrahepatic metastasis, (2) CTP functional class A or B, (3) normal renal function with a serum creatinine concentration < 1.5 mg/dL, and (4) no gross ascites by ultrasound or CT [24, 25]. Therapeutic information including benefits and risks was provided to individual patient based on shared decision making.…”
Section: Methodsmentioning
confidence: 99%
“…The Seldinger’s technique of arterial embolization was administered as standard TACE procedure [2325]. In brief, the four-French catheter (Terumo, Tokyo, Japan) were used for femoral artery puncture.…”
Section: Methodsmentioning
confidence: 99%
“…Indications and details of treatment procedures have been reported in our previous series . Briefly, SR was offered to patients with tumor(s) involving no more than three…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9][10][11][14][15][16] In our experience, tumour size, elevated INR and tumour hypovascularity on imaging study were found to be significant risk factors for increased mortality. CLIP score was found to be significant by univariate analysis, but not in the final analysis.…”
Section: O Ut C O Me Po St Tr a Nsc At H E T E R A R T E R I A L C H mentioning
confidence: 98%